Thermodynamic Characteristics of Oxidation and Combustion of Coal under Lean-Oxygen Conditions - Wang, Haiyan (ACS Omega, 2021)
[Image: see text] Coal spontaneous combustion (CSC) often occurs in environments that are poorly ventilated or under lean-oxygen environments in coal mines or coal seam outcrops. The understanding of the thermodynamic properties of CSC under lean-oxygen conditions is important to avoid safety and environmental problems. In this paper, the mass variation and critical temperature (the minimum temperature required for coal reaction in each stage) of six coals during CSC under lean-oxygen conditions were investigated using thermogravimetric methods. Furthermore, the thermodynamics parameters and kinetic compensation processes during CSC under lean-oxygen conditions were analyzed. The results showed that the oxidation and combustion of coal under lean-oxygen conditions was affected by the coal rank and oxygen concentration. The increase in the critical temperature was more significant when the oxygen concentration was reduced from 10 to 5%. The mechanism functions most likely to cause CSC at different oxygen concentrations were similar. The reaction mechanisms of high-rank coals at a low-temperature oxidation stage were more influenced by oxygen concentration than low-rank coals. Evaluations of kinetic behavior showed that activation energy decreased in a linear manner as the oxygen concentration decreased. The mathematical relationship between the activation energy and the pre-exponential factor indicated that there was a kinetic compensation process during CSC under lean-oxygen conditions. It is also worth noting that the effect of the coal rank on the thermodynamic characteristics of CSC is better than that of oxygen concentration. This work is helpful for enhancing the prediction and prevention of CSC.